Influence of Climate and Management on Patterns of Taxonomic and Functional Diversity of Recreational Park Vegetation - Ibsen, Peter C.; Borowy, Dorothy; Rochford, Mia; Swan, Christopher M.; Jenerette, G. Darrel (Frontiers in Ecology and Evolution, 2020)
Recreational urban parks support diverse assemblages of plants that through their functions, contribute beneficial services to billions of individuals throughout the world. Drivers of vegetation-derived services in parks are complex, as climate and park management interact with the functioning of multiple species of vegetation types. Yet, informal observations suggest that recreational parks are constructed consistently to specific principles of landscape design. Here we ask: what are the patterns of functional traits and vegetation diversity in cities of varying climate in the United States, and how do these patterns result in a consistent typology of recreational park? We hypothesized that increased aridity would exclude species not adapted to warm, dry climates, thereby reducing local, or alpha, taxonomic diversity and shifting community composition. However, a similar preference of park managers in the United States for suites of service-based functional traits leads to similarity of mean values of services traits in recreational parks among cities, regardless of climate differences. We tested this hypothesis by surveying lawn species, comprised of herbaceous turf and spontaneous plants, and woody species in fifteen recreational parks across Baltimore MD, Riverside CA, and Palm Springs CA, three cities that contain multiple parks but differ in regional climate. With increasing aridity, taxonomic alpha diversity decreased and plant physiology shifted, yet no differences were observed among most service-based functional traits. Among the cities surveyed, no significant differences were observed in functional dispersion of woody and spontaneous species or most service-based traits. Taxonomic composition differed in each city for all vegetation types, while suites of service-based traits differed between Baltimore and the two more arid cities of Riverside and Palm Springs. Our results suggest that across the U.S., service-based functional traits are consistent, even when arising from unique compositions and abundances of species in recreational parks. We interpret these results as an interaction between climate and the preferences of recreation park managers for services, creating a pattern of vegetation diversity where taxonomic alpha and beta diversity vary among regions while specific suites of services remain available.